Realizing technical synthesis and digital reproduction of the swimming movements based on OpenGL technology - Wu, C. X.; Zhou, X. D. (Advanced Materials Research, 2011)
Sports technique analysis refers to the technical diagnosis on the athletes` movements in order to enhance the scientificalness and rationality of the actions of sport skills. In this paper, the methods of its application into swimming events with different purposes and in different environments are given. After the athletes` abovewater and underwater kinematic parameters are obtained, first of all, the OpenGL technology is used to separate the athlete's movement technique from their sports environment and to digitally reproduce the technical movement synthesis, and then the key paddling route of the swimming athlete`s "paddling" motion technique is drawn.